Biocoating—A Critical Step Governing the Oral Delivery of Polymeric Nanoparticles (Small 26/2022). Issue 26 (1st July 2022) - Azagury, Aharon; Baptista, Cameron; Milovanovic, Kosta; Shin, Hyeseon; Morello, Peter; Perez‐Rogers, James; Goldenshtein, Victoria; Nguyen, Travis; Markel, Arianna; Rege, Soham; Hojsak, Stephanie; Perl, Alexander; et al.
Abstract : Biocoating In article number 2107559, Edith Mathiowitz and co‐workers characterize the effects of nanoparticles (NPs) interaction with gut mucins. Mucins biocoating alters the surface charge, effective size, mucosal diffusion coefficient, and the extent of NPs aggregation. The implementation of this natural phenomenon may improve in vitro to in vivo correlation and alleviate long‐lasting controversies regarding bioadhesive NPs and the appropriate surface charge for oral drug delivery.